2022
DOI: 10.1073/pnas.2121362119
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes degraded under high light maintain proteostasis by transcriptional regulation inArabidopsis

Abstract: Significance Photoinhibitory high light stress in plants leads to increases in markers of protein degradation and transcriptional up-regulation of proteases and proteolytic machinery, but protein homeostasis (proteostasis) of most enzymes is largely maintained under high light, so we know little about the metabolic consequences of it beyond photosystem damage. We developed a technique to look for rapid protein turnover events in response to high light through 13 C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…More generally, a recent analysis of high-light stress on chloroplast proteostasis found that when rates of N -pt protein turnover increase, there is generally upregulation in mRNA abundance for the corresponding N -pt genes. In contrast, increased turnover of plastid-encoded proteins was rarely associated with an increase in the corresponding plastid mRNAs ( 55 ). These observations are consistent with the hypothesis that mitochondria and plastids are relatively lacking in precise, short-term transcriptional control and that the large standing population of organellar mRNAs offers a means for rapid regulatory responses at a posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, a recent analysis of high-light stress on chloroplast proteostasis found that when rates of N -pt protein turnover increase, there is generally upregulation in mRNA abundance for the corresponding N -pt genes. In contrast, increased turnover of plastid-encoded proteins was rarely associated with an increase in the corresponding plastid mRNAs ( 55 ). These observations are consistent with the hypothesis that mitochondria and plastids are relatively lacking in precise, short-term transcriptional control and that the large standing population of organellar mRNAs offers a means for rapid regulatory responses at a posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not this would lead to gross changes in protein abundance is unclear, depending on the stability of the protein product (Li et al., 2017 ). Nonetheless, our observations suggest that the transcriptional compensation observed at genes encoding proteins degraded under high light, should result in elevated translation that contributes to maintaining proteostasis during stress (Li et al., 2022 ).…”
Section: Discussionmentioning
confidence: 81%
“…Whether or not this would lead to gross changes in protein abundance is unclear, depending on the stability of the protein product (51). Nonetheless, our observations suggest that the transcriptional compensation observed at genes encoding proteins degraded under high light, should result in elevated translation that contributes to maintaining proteostasis during stress (84).…”
Section: Discussionmentioning
confidence: 92%